Experimental study of blast mitigation by foamed concrete. Issue 2 (June 2016) - Tian, Xinbang; Li, Qingming; Lu, Zhongyuan; Wang, Zhihua
Field blast tests were performed to investigate the effects of foamed concrete panels on structural response. Foamed concrete specimen with two densities and aluminum-alloy front face sheet were studied. Effects of four key parameters, that is, blast impulse, foamed concrete density, thickness of foamed concrete panel, and the thickness of front face sheet, on structural response were studied using ballistic pendulum system and laser displacement transducer. Deformation of the back panel protected by foamed concrete and the failure modes of foamed concrete specimen when subjected to blast load were obtained. Experimental results indicate that foamed concrete can be used to attenuate blast load and reduce structural deformation effectively.